Efforts to Improve Initial Reading Skills through the Use of Flash Card Media in Group B Children at PAUD Az-Zahra Empat Lawang - Susi Yanti; Manto Manto (Universitas Muhammadiyah Enrekang, 2024)
The study examined how using flashcards in early reading helped children recognize and pronounce letters, convert syllables into words, read short sentences word for word, and distinguish vowels and consonants. Flashcards are used in commencement reading activities in Group B of Az-Zahra Empat Lawang Kindergarten to engage children and make learning fun. This study aims to provide an overview of the design, implementation, and assessment of learning aimed at improving the basic reading skills of young readers in Group B in PAUD Az-Zahra Empat Lawang using flashcard media. This research uses qualitative techniques in the form of qualitative descriptive study. The data collection method used is a form of qualitative descriptive research. The results showed that learning using flashcard media can improve children's early reading skills.